Effects of chemical defaunation on rumen fermentation pattern in cattle and buffaloes - Sahu, D S; Prasad, Krishna; Agrawal, I S; Verma, M L (The Indian Journal of Animal Sciences, 2012)
An experiment was designed to study the duration of effectiveness of sodium lauryl sulphate in defaunating the rumen contents and on the concentration of rumen metabolites. The rumen liquor samples were collected on 1, 10 and 20 days of administration of the chemical at, 0, 2, 4, 6 and 8 hr postfecding from fallnated and defaunated, fistulated bullocks in a 4-factor RBD. The rumen pH and total volatile fatty acids concentration in strained rumen liquor (SRL) did not differ significantly (P